Corporate citizenship and social responsibility policies in the United States of America. Issue 1 (6th March 2017) - Camilleri, Mark Anthony
Abstract : Purpose: The aim of this case study is to outline relevant regulatory guidelines on environmental, social and governance issues in the USA. This contribution includes a thorough analysis of several institutional frameworks and guiding principles that have been purposely developed to foster corporate citizenship behaviours. Design/methodology/approach: A case study methodology involved a broad analysis of US regulatory policies, voluntary instruments and soft laws that have stimulated organisations to implement and report their responsible behaviours. Findings: This contribution ties the corporate citizenship behaviours with the institutional and stakeholder theories. The case study evaluated the US's federal government, bureaus and its agencies' policies on human rights, health and social welfare, responsible supply chain and procurement of resources, anticorruption, bribery and fraudulent behaviours, energy and water conservation practices as well as environmental protection, among other issues. Research limitations/implications: Past research may have not sufficiently linked corporate citizenship with the corporate social responsibility (CSR) paradigm. This research reports how different US regulatory institutions and non-governmental organisations are pushing forward the social responsibility, environmental sustainability as well as the responsible corporate governance agenda. Originality/value: This research critically analyses US policy and regulatory instruments including relevant legislation and executive orders that are primarily intended to unlock corporate citizenship practices from business and industry. It has also provided a conceptual framework for the corporate citizenship notion. In conclusion, it implies that there are business and political cases for corporate citizenship.